Impaired immune reconstitution in HIV infection: the role of CD4+ T-cell-associated NKG2D ligands, CD4+ T-cell subsets imbalance, and immune function deficiency - Xu, Qianqian; Zhang, Qiuyue; Xu, Peng; Zhang, Tong; Wu, Hao; Zhang, Xin; Moog, Christiane; Su, Bin (Frontiers in Immunology, 2025)
ObjectiveThe role of natural killer (NK) cells, which mediate innate immunity, in the immune reconstitution of people living with HIV (PLWH) remains unclear. Our previous research indicated that early activation of CD56dimCD16dim/- NK cells plays an important role in the recovery of CD4+ T cells in immunological non-responders (INRs) after ART. This study mainly focuses on the profiles of cell receptors and their relative ligands for NK cells and CD4+ T cells exhibited on INRs and immunological responders (IRs) in order to analyze the impact of differential immune status on immune reconstitution in PLWH receiving ART.MethodsThis study included 66 PLWH who had been on ART for 4 years, comprising 32 INRs and 34 IRs. Using flow cytometry, we examined the expression of cell receptors and ligands for NK cells and CD4+ T cells in PBMCs, as well as the differentiation of CD4+ T cells.ResultsThe expression of NKG2D ligands, including MICA/B and ULBP2-5, on CD4+ T cells in INRs is elevated prior to ART. Further research found that the expression of CD95 on MICA/B+CD4+ T cells and ULBP2-5+CD4+ T cells was higher in INRs before ART compared to IRs. Simultaneously, the percentages of death receptor CD95 expression on MICA/B+CD4+ T cells and on ULBP2-5+CD4+ T cells before ART were negatively correlated with CD4+ T-cell counts and ΔCD4. Among the CD4+ T-cell subsets, an imbalance persists in the CD4+ Tcm and CD4+ Temra subsets in both INRs and IRs, before or after ART. CD4+ T cells exhibit elevated levels of activation, proliferation, exhaustion, and apoptosis prior to ART initiation. However, CD4+ T-cell activation and proliferation normalize post-ART, while apoptosis and exhaustion levels remain significantly elevated. Regardless of ART, the anti-apoptotic capacity of CD4+ T cells in INRs is still lower than that of IRs and healthy controls (HCs). Before ART, the frequency of CD31 expression on naive CD4+ T cells in INRs is lower than that in IRs and HCs. Following ART, the amounts of CD31+ Tn from CD4+ T cells remain impaired in both INRs and IRs compared to HCs.ConclusionThe upregulation of related ligands for the NKG2D receptor on CD4+ T cells in INRs is associated with increased susceptibility of CD4+ T cells to NK cell-mediated killing. CD95 may plays an important role in poor recovery of CD4+ T cells co-expressing NKG2D-related ligands. The imbalance in CD4+ Tcm and CD4+ Temra subset homeostasis and impaired CD31 expression on naive CD4+ T cells in INRs are associated with poor immune reconstitution outcomes.